2014
DOI: 10.9790/3013-04011044048
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative effect of Capsicum oleoresins compared with pure capsaicin

Abstract: Capsicum annum L, or hot

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…In the experiment, as proportion of carvacrol found in thyme ( Origanum vulgare ) essential oil, cinnamaldehyde found in cinnamon ( Cinnamomum zeylanicum ) essential oils, capsaicin bioactive substances found in chili paprika ( Capsicum annuum ) can vary in etheric oils due to reasons mentioned above, synthetic 99% carvactol, 98% cinnamaldehyde, 99% capsicum oleoresin (includes 6.6% capsaicin), which are identical to natural secondary metabolites were used. Because carvacrol and cinnamaldehyde are both digestive stimulants and can increase appetite as well as being antifunfgal [ 11 , 12 ], while capsicum oleoresin is endocrine and immune stimulant [ 13 , 14 ], and also antioxidant [ 15 ], lastly the mixture group can act synergistically with various combination of active substances, they were preferred [ 16 ]. On the other hand, in studies conducted with different plant extracts and etheric oils, it was found that sensory (tenderness, taste) and physical (toughness, firmness) properties of broiler meat were not affected in general [ 17 ], and some of the chemical properties (decreased MDA, increased PUFA) were improved [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, as proportion of carvacrol found in thyme ( Origanum vulgare ) essential oil, cinnamaldehyde found in cinnamon ( Cinnamomum zeylanicum ) essential oils, capsaicin bioactive substances found in chili paprika ( Capsicum annuum ) can vary in etheric oils due to reasons mentioned above, synthetic 99% carvactol, 98% cinnamaldehyde, 99% capsicum oleoresin (includes 6.6% capsaicin), which are identical to natural secondary metabolites were used. Because carvacrol and cinnamaldehyde are both digestive stimulants and can increase appetite as well as being antifunfgal [ 11 , 12 ], while capsicum oleoresin is endocrine and immune stimulant [ 13 , 14 ], and also antioxidant [ 15 ], lastly the mixture group can act synergistically with various combination of active substances, they were preferred [ 16 ]. On the other hand, in studies conducted with different plant extracts and etheric oils, it was found that sensory (tenderness, taste) and physical (toughness, firmness) properties of broiler meat were not affected in general [ 17 ], and some of the chemical properties (decreased MDA, increased PUFA) were improved [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional uses or phytochemical properties of capsaicin from several literature reviews are described antibacterial,[ 25 26 ] anticancer,[ 27 28 ] antidiabetic,[ 29 30 ] antifungal,[ 31 32 ] antihypertensive,[ 33 34 ] anti-inflammation,[ 35 36 37 ] antioxidant,[ 38 39 ] and antipain activities. [ 40 41 42 ] Moreover, it can be used for the treatment of cardiovascular[ 43 44 ] and hepatic diseases.…”
Section: Traditional Usesmentioning
confidence: 99%
“…[12][13][14] Among the different topographic features,a rrays of bulges or pillars and grooved patterns at the nanoscale are considered the most effective in promoting axonal guidance and elongation because they can provide more sensing targets and appropriate contact areas for the growth cones of neurites. [15][16][17] It is documented that the outgrowth of neurites can be regulated at both subcellular and cellular levels by acting on the growth cones and axons,r espectively. [18] As such, the substrate most effective in promoting neurite outgrowth should contain topographic features with two different sizes,about 1 mmand 200 nm, to match the dimensions of typical axons and the filopodia of growth cones.…”
Section: Introductionmentioning
confidence: 99%